2005
DOI: 10.1007/s11240-005-1372-x
|View full text |Cite
|
Sign up to set email alerts
|

An improved system for the in vitro regeneration of Thapsia garganica via direct organogenesis – influence of auxins and cytokinins

Abstract: An improved protocol for mass multiplication directly from leaf material of Thapsia garganica was developed. Using factorial experimentation, auxins (NAA, IAA, 2,4-D D ) and cytokinin (BA, kinetin) combinations at 0-2 mg l )1 added to Murashige and Skoog (MS) medium with 30 g l )1 sucrose and 8 g l )1 agar (pH 5.8) were tested for their effect on direct regeneration on leaflet and petiole explants. Of the media tested, the 0.5:1.5 NAA:BA medium was comparable for direct shoot organogenesis to the 2 mg l )1 kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…The present study showed that the appropriate concentrations of combination of auxin, gibberellins and cytokinin are essential for the direct and efficient regeneration of explants without callus formation. The presence of a cytokinin in the medium is essential for adventitious shoot formation (Makunga et al 2005). The rate of regeneration was low on MS solid medium supplemented with single PGR whereas the regeneration rate was high on the MS solid medium supplemented with NAA in combination with BAP, zeatin and GA 3 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that the appropriate concentrations of combination of auxin, gibberellins and cytokinin are essential for the direct and efficient regeneration of explants without callus formation. The presence of a cytokinin in the medium is essential for adventitious shoot formation (Makunga et al 2005). The rate of regeneration was low on MS solid medium supplemented with single PGR whereas the regeneration rate was high on the MS solid medium supplemented with NAA in combination with BAP, zeatin and GA 3 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The latter PGR combination has been shown to induce hyperhydric plants (Makunga et al 2005) (see also Fig. 2B).…”
Section: Pre-acclimatizationmentioning
confidence: 89%
“…The first successful report on the tissue culture of T. garganica produced somatic embryos but plantlet production and acclimatization was not investigated (Jäger et al 1993). The only other reports on the successful regeneration of plantlets via tissue culture (Makunga et al 2003(Makunga et al , 2005) emanated from our laboratories and obstacles pertaining to low incidence of rooting of plantlets (32% rooted plantlets); reproducibility of the rooting regime; and, poor establishment of in vitro propagated plants after acclimatization as a result of fungal infections were reported on (Makunga et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…halophilus are those of Imani et al (2001) and Thi and Pleschka (2005). As it is well-known, somatic embryogenesis was first achieved in carrot (Reinert 1958;Steward et al 1958), and since then, many reports about micropropagation and somatic embryogenesis have been published for carrot and other Apiaceae species (Ekiert 2000;Thorpe and Stasolla 2001;Makunga et al 2005).…”
Section: Introductionmentioning
confidence: 99%